Biosynthesis and structural characterization of Ag nanoparticles from white rot fungi - Chan, Stephanie; Don, M. (Elsevier, 2013)
Five species of white rot fungi were screened for their capability to synthesize Ag nanoparticles (AgNPs). Three modes of AgNP bioreduction were developed. Pycnoporus sanguineus is found as a potential candidate for the synthesis of AgNPs with a yield at 98.9%. The synthesized AgNPs were characterized using UV–vis spectroscopy, DLS, FTIR, TEM, and SEM. Results showed that AgNP absorption band was located at a peak of 420 nm. Both the SEM and TEM confirmed that the formation of AgNPs were mainly spherical with average diameters of 52.8–103.3 nm. The signals of silver atoms' presence in the mycelium were observed by SEM-EDS spectrum.